Binding and lubrication of biomimetic boundary lubricants on articular cartilage. Issue 3 (14th September 2016) - Samaroo, Kirk J.; Tan, Mingchee; Putnam, David; Bonassar, Lawrence J.
ABSTRACT: The glycoprotein, lubricin, is the primary boundary lubricant of articular cartilage and has been shown to prevent cartilage damage after joint injury. In this study, a library of eight bottle‐brush copolymers were synthesized to mimic the structure and function of lubricin. Polyethylene glycol (PEG) grafted onto a polyacrylic acid (pAA) core mimicked the hydrophilic mucin‐like domain of lubricin, and a thiol terminus anchored the polymers to cartilage surfaces much like lubricin's C‐terminus. These copolymers, abbreviated as pAA‐ g ‐PEG, rapidly bound to cartilage surfaces with binding time constants ranging from 20 to 39 min, and affected lubrication under boundary mode conditions with coefficients of friction ranging from 0.140 ± 0.024 to 0.248 ± 0.030. Binding and lubrication were highly correlated ( r 2  = 0.89–0.99), showing that boundary lubrication in this case strongly depends on the binding of the lubricant to the surface. Along with time‐dependent and dose‐dependent behavior, lubrication and binding of the lubricin‐mimetics also depended on copolymer structural parameters including pAA backbone length, PEG side chain length, and PEG:AA brush density. Polymers with larger backbone sizes, brush sizes, or brush densities took longer to bind ( p  < 0.05). Six of the eight polymers reduced friction relative to denuded cartilage plugs ( p  < 0.05), suggesting their potential to lubricate and protect cartilage in vivo. In copolymers with shorter pAA backbones, increasing hydrodynamic size inhibited lubrication ( p  < 0.08), while the opposite was observed in copolymers with longer backbones ( p  < 0.05). These polymers show similar in vitro lubricating efficacy as recombinant lubricins and as such have potential for in vivo treatment of post‐traumatic osteoarthritis. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:548–557, 2017.